Access, understanding, promotion and maintenance of good health: Evaluation of knowledge transfer of people with intellectual disabilities to bridge the health information and disease prevention in public health - Dam, Lisa T.; Heidler, Petra; King, Isabel (Frontiers in Public Health, 2022)
The importance of patient empowerment among people with intellectual disabilities (ID) is steadily growing, yet multiple health and health literacy challenges still make this population more vulnerable to health disparities. Inadequate access to essential health and other basic services and the lack of involvement in health and educational research are some of the most crucial factors contributing to this inequality. A greater effort must be made to include people with ID in health literacy and communication research, preliminary focusing on language, including pictorial language. This community case study aimed to document the experiences of answering a pilot questionnaire to evaluate the problems of people with mild to moderate ID, 6A00.0 and 6A00.1 according to ICD-11. Our results show that most patients acquire health information from their physician or a medical professional. In preparing appropriate questionnaires, special education teachers can give valuable insight. However, participants were easily distracted and needed support in focusing on the questionnaire. Easy-to-read language, a simple format, big fonts and the presence of confidential caretakers are needed. This indicates, that semi-structured interviews with a trained interviewer might be most suitable for measuring the knowledge transfer of people with ID. The results of this case study highlight the need to develop an appropriate questionnaire and emphasize the need for a continued dialogue between people with ID and healthcare providers.